Pengaruh Pembelajaran Daring Dan Motivasi Belajar Di Masa Pandemi Covid-19 Terhadap Prestasi Belajar Mahasiswa Program Studi Pendidikan Teknik Bangunan - Wildan Baladan; Sukadi Sukadi; Mardiani Mardiani; Rieske Iswardhany (Jurnal Pendidikan Teknik Bangunan, 2021)
The goal of the study was to see how much of an impact online learning and learning motivation had on student achievement in the Building Engineering Education Study Program at the Indonesian Education University during the covid-19 pandemic. Learning achievement is evidence of someone's success after going through the learning process. This study employs a quantitative approach and employs a descriptive static research method survey. The study used 38 students from the 2018 Building Engineering Education study program as a sample. A questionnaire was used to collect data for the study, as well as documentation in the form of the 5th semester student achievement index value. According to the study's findings, (1) the average online learning score of 3.74 falls into the high interpretation category, (2) the average learning motivation score of 3.49 falls into the high interpretation category, (3) The average learning achievement score of 3.57 falls into the category of very good interpretation. With an coefficient determination of 0.044 or 4.4 percent, there is no significant effect of online learning and learning motivation on learning achievement.